The foundations of econometric analysis - Hendry, David F.; Morgan, Mary S.; Morgan, Mary S. (Cambridge University Press, 1994)
In this compelling book, David Hendry and Mary Morgan bring together the classic papers of the pioneer econometricians, some of which have never been published before. Together, these papers form the foundations of econometric thought. They are essential reading for anyone seeking to understand the aims, method and methodology of econometrics and the development of this statistical approach in economics. However, because they are technically straightforward, the book is also accessible to students and non-specialists. An editorial commentary places the readings in their historical context and indicates the continuing relevance of these early, yet highly sophisticated, works for current econometric analysis. While this book provides a companion volume to Mary Morgan's acclaimed The History of Econometric Ideas, the editors' commentary both adds to that earlier volume and also provides a stand-alone and synthetic account of the development of econometrics.